2016
DOI: 10.1039/c5cs00537j
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear PdIcomplexes with bridging allyl and related ligands

Abstract: There are many important synthetic methods that utilize palladium catalysts. In most of these reactions, the palladium species are proposed to exist exclusively in either the Pd(0) or Pd(II) oxidation states. However, in the last decade, dinuclear Pd(I) complexes have repeatedly been isolated from reaction mixtures previously suggested to involve only species in the Pd(0) and Pd(II) oxidation states. As a consequence, in order to design improved catalysts there is considerable interest in understanding the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 129 publications
1
36
0
Order By: Relevance
“…Catalytic transformations using these catalysts, such as addition, polymerization, allylic substitution, cross coupling, and C–H substitution reactions, significantly contribute to the production of useful organic chemicals in industry. Interestingly, several dinuclear Pd(I) and Ni(I) complexes have been reported to demonstrate notably higher activity as precatalysts compared to typical monomeric zerovalent or divalent metal complexes [ 11 , 12 , 13 , 14 , 15 , 16 ]. Detailed mechanistic studies revealed that dinuclear or mononuclear active catalysts are generated from the corresponding dinuclear precatalysts to achieve highly efficient and/or selective catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic transformations using these catalysts, such as addition, polymerization, allylic substitution, cross coupling, and C–H substitution reactions, significantly contribute to the production of useful organic chemicals in industry. Interestingly, several dinuclear Pd(I) and Ni(I) complexes have been reported to demonstrate notably higher activity as precatalysts compared to typical monomeric zerovalent or divalent metal complexes [ 11 , 12 , 13 , 14 , 15 , 16 ]. Detailed mechanistic studies revealed that dinuclear or mononuclear active catalysts are generated from the corresponding dinuclear precatalysts to achieve highly efficient and/or selective catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Several other reports proposed that heterolytic or homolytic cleavage of the metal–metal bond of dinuclear Pd(I) or Ni(I) complexes could produce active metal species in situ, such as highly unsaturated “mono-ligated metal complexes”. However, the chemistries of dinuclear Ni(I) and Pd(I) complexes in catalysis have not been classified and compared with each other, although the chemistry of such nickel and palladium complexes has been summarized individually [ 11 , 12 , 13 , 14 , 15 , 16 ]. Therefore, the survey and comparison of the reactivity and catalytic performance of dinuclear nickel(I) and palladium(I) complexes, as well as their generation processes and structures, should be useful and informative.…”
Section: Introductionmentioning
confidence: 99%
“…The first description of the activation of Pd–allyl complexes, using an alternate weak base (K 2 CO 3 ), was performed by Colacot and co‐workers and was followed by similar reports . In the course of the preparation of the dinuclear Pd I complex [Pd 2 (IPr) 2 (η 3 ‐cin)Cl] (IPr=1,3‐bis(2,6‐diisopropyl‐phenyl)imidazol‐2‐ylidene; cin=cinnamyl), Hazari and co‐workers proposed an equilibrium between the Pd I ‐dimer and the catalytically active Pd 0 –NHC intermediate by a comproportionation/disproportionation reaction with unreactive [Pd(IPr)(cin)Cl] . In this context, this study suggested the activation pathway of [Pd(NHC)(R‐allyl)Cl] to proceed as depicted in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, chemists have great interest in the use of bimetallic compounds as catalysts to impart new reactivity of chemical reactions. Among various transition metal ions, dipalladium complexes have received much attention due to the remarkable activity of this metal ions . Few di‐nuclear palladium complexes exhibit the catalytic activities in cross‐coupling, olefin polymerization, and C‐H activation .…”
Section: Introductionmentioning
confidence: 99%